Procyanidin A1 and its digestive products alleviate acrylamide-induced IPEC-J2 cell damage through regulating Keap1/Nrf2 pathway - Fangfang Yan; Qun Lu; Chengming Wang; Rui Liu (Food Science and Human Wellness)
Our previous study has revealed that procyanidin A1 (A1) and its simulated digestive product (D-A1) can alleviate acrylamide (ACR)-induced intestine cell damage. However, the underlying mechanism remains unknown. In this study, we elucidated the molecular mechanism for A1 and D-A1 to alleviate ACR-stimulated IPEC-J2 cell damage. ACR slightly activated nuclear factor erythroid 2-related factor 2 (Nrf2) signaling and its target genes, but this activation could not reduce intestine cell damage. A1 and D-A1 could alleviate ACR-induced cell damage, but the effect was abrogated in cells transiently transfected with Nrf2 small interfering RNA (siRNA). Further investigation confirmed that A1 and D-A1 interacted with Kelch-like ECH-associated protein 1 (Keap1), which boosted the stabilization of Nrf2, subsequently promoted the translocation of Nrf2 into the nucleus, and further increased the expression of antioxidant proteins, thereby inhibiting glutathione (GSH) consumption, maintaining redox balance and eventually alleviating ACR-induced cell damage. Importantly, there was no difference between A1 and D-A1 treated groups, indicating that A1 can tolerate gastrointestinal digestion and may be a potential compound to limit the toxicity of ACR.